Banking Crises and Bank Resolution : Experiences in Some Transition Economies. (IMF Working Papers; Working Paper ;, 2002)
Like most transition economies, Bulgaria, Lithuania, and Mongolia suffered severe banking crises, which had to be resolved before growth could resume. The macroeconomic and institutional failings that led to these crises are described, and parallels are drawn with the causes of banking crises in industrial and developing countries. Resolving the crises proved technically and politically difficult, and setbacks occurred. Successful resolution required the implementation of a comprehensive and decisive strategy, involving thorough-going bank restructuring, heavy fiscal costs, and institutional and legal reforms.